A case of isolated hypoglossal nerve palsy with acute lymphoblastic leukemia - Suzuki, Masahiko; Hashimoto, Masaya; Sakimoto, Yoshihiro; Yoshioka, Masayuki; Kawasaki, Keiichi; Kamii, Yasuhiro (Rinsho Shinkeigaku, 2013)
We report a case of isolated hypoglossal nerve palsy with acute lymphoblastic leukemia. A 47-year-old woman had fever unknown origin during two months. Her tongue bent to the right and cephalalgia developed. She complained unable to speech and swallow. On admission, right isolated hypoglossal nerve palsy presented. Blood examination showed the mild elevation of CRP and soluble IL2 receptor. Examination of cerebrospinal fluid was negative. Gadolinium enhanced magnetic resonance imaging (MRI) of brain showed abnormal intensity on sphenoid bone. 2-[18F] fluoro-2-deoxy-D-glucose (FDG)-positron emission tomography (PET) showed abnormal accumulation on sphenoid bone, spleen, the left supraclavicular node, mesenteric lymph node. Blast cells appeared in peripheral blood afterwards. Acute lymphatic leukemia (ALL) was diagnosed by bone marrow biopsy. The central nervous system disorder by ALL tends to the invasion to meninges or cerebrovascular disorder. This is the first case report that isolated hypoglossal nerve paralysis resulted from ALL.